TEKNIK-TEKNIK REMEDIASI SEDIMEN TERKONTAMINASI LOGAM BERAT - Harmesa Harmesa (Pusat Penelitian Oseanografi LIPI, 2020)
Sediments are important in influencing changes and movements of the heavy metals in the aquatic environment. Heavy metals contamination of the sediments has negative ecological impacts on the environment. Therefore, economical, effective, and environmentally friendly remediation processes are needed. Purposes of the remediation are to reduce toxicity, bioavailability, and mobility of the metals from the polluted sediments. The remediations are developed using physical-chemical, biological and combination of both techniques. Physical-chemical techniques are carried out to decrease the stability of contaminated substances. Biological techniques or known as bioremediation are conducted through biological processes of plants, animals, and microorganisms. While the combination of both respective techniques, can produce maximum benefits and increase remediation efficiency.